KESIAPAN BELAJAR SISWA YANG TINGGAL DI KOS DALAM PROSES PEMBELAJARAN DAN IMPLIKASINYA TERHADAP BIMBINGAN DAN KONSELING - Fauziah . (JURNAL HANDAYANI PGSD FIP UNIMED, 2016)
Learning readiness can be regarded as the initial condition in a learning activity which prepares the students to interact and give response to achieve the learning goals. This research was intended to describe and compare the learning readiness of the students living in boarding house.. This was a descriptive research which used quantitative approach.The result of data analysis revealed that the learning readiness of the students living in boarding house was in good category. It was implied that the results of this research could be taken into account by the guidance and counseling teachers for organizing the activities of guidance and counseling program in maintaining, developing and increasing the students readiness to learn.          Keywords: Implication, Learning Readiness